Difficult birth is the main contributor to birth‐related fracture and accidents to other neonatal fractures. (29th February 2020) - Högberg, Ulf; Fellman, Vineta; Thiblin, Ingemar; Karlsson, Ruth; Wester, Knut
Abstract: Aim: Specific birth‐related fractures have been studied; underestimates might be a problem. We aimed to assess all fractures diagnosed as birth‐related as well as other neonatal fractures. Methods: A population‐based study on all infants born in Sweden 1997‐2014; data were retrieved from the Swedish Health Registers (10th version of International Classification of Diseases. Outcome measures were birth‐related fractures (ICD‐10 P‐codes) and other neonatal fractures (ICD‐10 S‐codes). Results: The overall fracture incidence was 2.9 per 1000 live birth (N = 5336); 92.6% had P‐codes and 7.4% (S‐codes). Some birth‐related fractures were diagnosed beyond the neonatal period. Other neonatal fractures could have been birth‐related. Clavicle fracture (88.8%) was associated with adverse maternal and infant anthropometrics and birth complications. The few neonates with rib fractures all had concomitant clavicle fracture. For skull fractures, a minor part was birth‐related and most were associated with accidents. Half of the long bone fractures were associated with accidents. Birth‐related femur fractures were associated with bone fragility risk factors. Five infants with abuse diagnoses had fractures: skull (4), long bone (2) and rib (1). Conclusion: Birth‐related and other neonatal fractures are rarely diagnosed. Difficult birth is the main contributor to birth‐related fracture and accidents to other neonatal fractures.